UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI HITUNG CAMPURAN MENGGUNAKAN METODE DRILL DENGAN BERBANTUAN MEDIA PUZZLE DI KELAS IV - Yulianti, Dewi; Andi Nurwati; Febry Rizki Susanti Kalaka (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2025)
This research aims to improve student learning outcomes in mixed arithmetic material using the drill method with the help of class IV puzzle media at SDN 07 Limboto Bongohulawa. It is hoped that the drill method with the help of puzzle media can improve student learning outcomes. This research method uses classroom action research (PTK) which was carried out in class IV at SDN 7 Limboto, with several stages including: (1) planning stage, (2) action implementation stage, (3) observation stage, and (4) reflection stage. The subjects in this research were all class IV students with a total of 16 students. The data collection techniques used in this research are observation, tests and documentation. The data analysis technique used in this research is descriptive qualitative. The results of this research show that learning using the drill method with the help of puzzle media can improve the quality of mathematics learning in mixed arithmetic operations material, which can be seen in the increase in completeness in the pre-cycle, 18.75%, increasing in cycle I to 50% and in cycle II increasing to 87%. . Thus, student learning outcomes and analysis of observation observation sheets improve in a better direction by implementing the use of the drill method with the help of puzzle media.